Distribution and Seasonal Variations of Argas persicus in Senegal - A. Gueye; M. Sylla; A. Diouf; I. Touré; J.L. Camicas (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2004)
This study reports on the habitat, distribution and seasonal abundance variations of Argas persicus (Oken, 1818) in Senegal. Traditional fowl houses – habitat of this tick species – were characterized in rural areas and various models were described: the bits-and-pieces model, thorn-branches model, weaved-plants models, and clay-made models. The distribution based on the square-degree scale indicated that the presence and abundance of Argas persicus mainly concerned the northern half of the country, whereas it was rare in the southern part. The seasonal variation of ticks was monitored for 17 months in the Sahelian zone. Tick removing and collecting from 50 fowls were performed every month for five minutes in each of the 30 fowl houses. They showed an all year round activity of Argas persicus. Examination of 200 blood smears in indigenous fowls, during the dry as well as the rainy seasons, did not indicate the presence of blood parasites. However, modern poultry production units located in the same areas were faced with epizootics of avian spirochetosis.